Audit Report Lag and Audit Fee Analysis Before and After the Implementation of Key Audit Matters in Indonesia - Loverita, Vindy Felycia; Januarti, Indira (Jurnal Dinamika Akuntansi dan Bisnis, 2024)
This study aims to examine the differences in audit report lag and audit fees in the year before and after the implementation of Key Audit Matters (KAM) in independent auditor reports. Provisions regarding KAM disclosure in Indonesia began with the 2022 financial reports. The population for this study includes all companies listed on the Indonesian Stock Exchange for the years 2021 and 2022. The dataset used in this research comprises 966 observations, consisting of 483 companies for each period (2021 and 2022). Using the Wilcoxon signed-rank test, the results indicate that the audit report lag was longer in the year before KAM communication compared to the year after its implementation. This finding could be attributed to the impact of the COVID-19 pandemic and the additional one-month extension granted by the Financial Services Authority (OJK) for the submission of audited financial reports. The results show that audit fees increased following the implementation of KAM. This suggests that auditors incur higher costs when required to include KAM in their audit opinions. This research highlights the implications of KAM communication on audit processes, including timeframes and associated costs.